2020
DOI: 10.3390/w12072008
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir-Induced Hydrological Alterations Using Ecologically Related Hydrologic Metrics: Case Study in the Beijiang River, China

Abstract: Anthropogenic activities have a tremendous impact on water ecosystems worldwide, especially in China. To quantitatively evaluate the hydrological alteration connected with aquatic lives and river ecological risks, we took the Beijiang River located in South China as the case study and used ecosurplus (defined as ecological carrying capacity exceeding ecological consumption)/ecodeficit (defined as ecological consumption exceeding carrying capacity) and Indicators of Hydrological Alterations to evaluate hydrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…According to Figure 7, the low flow rate contributed more to the eco‐surplus, whereas the high flow rate contributed more to the eco‐deficit. These findings are similar to those of Du et al (2020).…”
Section: Resultssupporting
confidence: 93%
“…According to Figure 7, the low flow rate contributed more to the eco‐surplus, whereas the high flow rate contributed more to the eco‐deficit. These findings are similar to those of Du et al (2020).…”
Section: Resultssupporting
confidence: 93%
“…DRGS b and PRGS b watersheds with 216 and 174 points, respectively, gained the rst ranks and were selected as the most critical watersheds in study area. However, in these watersheds in the pre-dam periods, BSA based on GT showed the lowest score and no critical condition was observed in these watersheds ( The box plot related to BSA points also showed that the highest range of changes (BSA = 5) was observed in the watersheds affected by the dam construction (Du et al, 2020;Villablanca et al, 2022) and even in DRGS b , the range of changes in BSA points was very low and con rmed the critical condition in this watershed. However, in the stations without the effect of the dam (DRGS a and PRGS a ), the range of changes in BSA scores was observed in low scores (1 to 2) (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…IHA has good applicability of hydrological data (water levels and flow) and is a quantitative index system for hydrological regime that is mature and widely used worldwide (Cheng et al 2019). It uses 33 indicators to reflect the hydrological regime of the river from 5 aspects: magnitude, duration, occurrence time, frequency and change rate (Du et al 2020). Referring to the selection principle and the ecological connotation of each indicator in IHA, we proposed 11 indicators to quantify the runoff from the base flow and the flood pulses, as shown in Table 3.…”
Section: Flood Pulse Indicators (Fpi)mentioning
confidence: 99%
“…According to the flood pulse theory, pulses formed in the rising or falling flood is the main driving force for biological survival, ecosystem interaction and productivity . Therefore, it is necessary to carry out a quantitative analysis on flood pulses, which can be divided into indicator selection, sample division and degree of change assessment (Du et al 2020). The only recognized flood pulse index system is the Indicators of Hydrologic Alteration (IHA) (Cheng et al 2019).…”
Section: Introductionmentioning
confidence: 99%